Novel calibration and color adaptation schemes in three-fringe RGB photoelasticity. (March 2015) - Swain, Digendranath; Thomas, Binu P.; Philip, Jeby; Pillai, S. Annamala
Abstract: Isochromatic demodulation in digital photoelasticity using RGB calibration is a two step process. The first step involves the construction of a look-up table (LUT) from a calibration experiment. In the second step, isochromatic data is demodulated by matching the colors of an analysis image with the colors existing in the LUT. As actual test and calibration experiment tint conditions vary due to different sources, color adaptation techniques for modifying an existing primary LUT are employed. However, the primary LUT is still generated from bending experiments. In this paper, RGB demodulation based on a theoretically constructed LUT has been attempted to exploit the advantages of color adaptation schemes. Thereby, the experimental mode of LUT generation and some uncertainties therein can be minimized. Additionally, a new color adaptation algorithm is proposed using quadratic Lagrangian interpolation polynomials, which is numerically better than the two-point linear interpolations available in the literature. The new calibration and color adaptation schemes are validated and applied to demodulate fringe orders in live models and stress frozen slices. Abstract : Highlights: A theoretical calibration procedure is proposed for generating RGB LUTs. It is useful when experimental LUTs are no more valid due to tint variations. Certain issues can be minimized during the generation of experimental LUTs. 3p-color adaptation scheme proposed using quadratic Lagrangian polynomials. Proposed LUT and color adaptation schemes are used to analyze DF & BF images.